Role of Mason-Pfizer monkey virus CA-NC spacer peptide-like domain in assembly of immature particles - Strohalmová-Bohmová, Karolína; Spiwok, Vojtěch; Lepšík, Martin; Hadravová, Romana; Křížová, Ivana; Ulbrich, Pavel; Pichová, Iva; Bednárová, Lucie; Ruml, Tomáš; Rumlová, Michaela (Journal of virology, 2014)
UNLABELLED: The hexameric lattice of an immature retroviral particle consists of Gag polyprotein, which is the precursor of all viral structural proteins. Lentiviral and alpharetroviral Gag proteins contain a peptide sequence called the spacer peptide (SP), which is localized between the capsid (CA) and nucleocapsid (NC) domains. SP plays a critical role in intermolecular interactions during the assembly of immature particles of several retroviruses. Published models of supramolecular structures of immature particles suggest that in lentiviruses and alpharetroviruses, SP adopts a rod-like six-helix bundle organization. In contrast, Mason-Pfizer monkey virus (M-PMV), a betaretrovirus that assembles in the cytoplasm, does not contain a distinct SP sequence, and the CA-NC connecting region is not organized into a clear rod-like structure. Nevertheless, the CA-NC junction comprises a sequence critical for assembly of immature M-PMV particles. In the present work, we characterized this region, called the SP-like domain, in detail. We provide biochemical data confirming the critical role of the M-PMV SP-like domain in immature particle assembly, release, processing, and infectivity. Circular dichroism spectroscopy revealed that, in contrast to the SP regions of other retroviruses, a short SP-like domain-derived peptide (SPLP) does not form a purely helical structure in aqueous or helix-promoting solution. Using 8-Å cryo-electron microscopy density maps of immature M-PMV particles, we prepared computational models of the SP-like domain and indicate the structural features required for M-PMV immature particle assembly. IMPORTANCE: Retroviruses such as HIV-1 are of great medical importance. Using Mason-Pfizer monkey virus (M-PMV) as a model retrovirus, we provide biochemical and structural data confirming the general relevance of a short segment of the structural polyprotein Gag for retrovirus assembly and infectivity. Although this segment is critical for assembly of immature particles of lentiviruses, alpharetroviruses, and betaretroviruses, the organization of this domain is strikingly different. A previously published electron microscopic structure of an immature M-PMV particle allowed us to model this important region into the electron density map. The data presented here help explain the different packing of the Gag segments of various retroviruses, such as HIV, Rous sarcoma virus (RSV), and M-PMV. Such knowledge contributes to understanding the importance of this region and its structural flexibility among retroviral species. The region might play a key role in Gag-Gag interactions, leading to different morphological pathways of immature particle assembly.
Keywords: Mason-Pfizer monkey virus; Virus Release; Nucleocapsid Proteins; uvolnění viru z buňky; Protein Conformation; Masonův-Pfizerův opičí virus; nukleokapsida - proteiny; Circular Dichroism; konformace proteinů; molekulární modely; sestavení viru; Models, Molecular; elektronová kryomikroskopie; Virus Assembly; virové plášťové proteiny; Cryoelectron Microscopy; Capsid Proteins; cirkulární dichroismus